SURXONDARYO VILOYATI DEGRADATSIYAGA UCHRAGAN O‘TLOQI TUPROQLARINING AYRIM FIZIK XOSSALARI. (AGROINNOVATSIYА, 2024)
The article presents the results of the study of the current state, morphological characteristics, and general physical properties of low-salinity soils in Angor District, Surkhondarya Region, and also comments on the research conducted in our country in this regard. Also, the results of the study on soil properties that change in the soil as a result of planting the same type of crop for many years are presented.